Analisis Penyebab Kesulitan Menulis Huruf Tegak Bersambung pada Siswa Kelas II SDN Sidodadi 1/153 - Elvira Oliviasari; Yossy Novita Surya Rahmawati; Andika Adinanda Siswoyo (ARZUSIN, 2025)
The ability to write cursive letters is a fundamental skill in elementary education, playing a crucial role in the development of fine motor skills, handwriting neatness, and writing speed, all of which impact students’ overall academic achievement. This study aims to identify the factors causing difficulties in writing cursive letters among second-grade students at SDN Sidodadi 1/153 Surabaya. A qualitative case study approach was employed, focusing on a single class group. Observations revealed that students’ writing abilities fell into three categories: high, moderate, and low. Students in the high category demonstrated neat and consistent handwriting, while the moderate category was characterized by irregular letter size and inconsistent spacing between words. The low category featured handwriting that was difficult to read due to untidiness, uneven letter sizes, and irregular spacing between letters. The factors contributing to writing difficulties were divided into internal and external factors. Internal factors included weak fine motor skills, low interest and motivation, insufficient writing practice, and limited understanding of cursive writing rules. External factors, identified through interviews, included excessive gadget use, limited parental involvement in home learning, and less interactive teaching methods. This study highlights the importance of a holistic and collaborative learning approach involving teachers, parents, and the environment to address students’ difficulties in writing cursive letters.